2020
DOI: 10.1061/(asce)co.1943-7862.0001844
|View full text |Cite
|
Sign up to set email alerts
|

Augmented and Virtual Reality in Construction: Drivers and Limitations for Industry Adoption

Abstract: Augmented and virtual reality have the potential to provide a step-change in productivity in the construction sector; however, the level of adoption is very low. This paper presents a systematic study of the factors that limit and drive adoption in the construction sectorspecific context. A mixed research method was employed, combining qualitative and quantitative data collection and analysis. Eight focus groups with 54 experts and an online questionnaire were conducted. Forty-two limiting and driving factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 77 publications
(73 reference statements)
2
84
0
1
Order By: Relevance
“…Most research and devices were in the experiment and prototype phase yet not applied to practical site construction. The main obstacle to adopting AR technologies during construction was the high expense and immature devices (Manuel Davila Delgado et al, 2020). Developing rapidly in recent years, AR devices suitable for construction are already commercially available.…”
Section: Figure 7 | Experiments Of Connection Between Ar Devices and Sensorsmentioning
confidence: 99%
“…Most research and devices were in the experiment and prototype phase yet not applied to practical site construction. The main obstacle to adopting AR technologies during construction was the high expense and immature devices (Manuel Davila Delgado et al, 2020). Developing rapidly in recent years, AR devices suitable for construction are already commercially available.…”
Section: Figure 7 | Experiments Of Connection Between Ar Devices and Sensorsmentioning
confidence: 99%
“…Augmented reality (AR) and virtual reality (VR) are two essential components that will boost the construction industry and have the ability to introduce innovative productivity in the construction industry [112]. AR is comprised of real-world experience, whereas VR is comprised of a completely immersive experience that completely isolates the user from the physical world.…”
Section: Bim Integration With Virtual Environmentmentioning
confidence: 99%
“…Davila Delgado et al (2020) represented that low rates of adoption and acceptance are partly caused by a lack of feasibility. (Noghabaei et al, 2020) examined the actual cost of implementation and revealed numerous complex and interrelated factors that present insuperable barriers to the development of suitable mitigating actions (Davila Delgado et al, 2020). Yet, the AECO industry relies on digital modelling, simulation and visual communication which has attracted research enquiry into applying VR technology to AECO applications from a "usefulness of technology" perspective (Al-Adhami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%